THE POWER OF DIGITAL STORYTELLING IN ENGAGING AND MOTIVATING YOUNG LEARNERS TO LEARN ENGLISH - Purnawan, Komang Ari; Artini, Luh Putu; Indrayani, Luh (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2026)
The development of digital technology in education offers opportunities to create more engaging and meaningful English learning for early childhood. One approach that has gained attention is digital storytelling, which integrates visual, audio, animation, and contextual narrative elements. Despite its growing use, comprehensive studies examining its role in enhancing engagement and motivation among young learners remain limited. Therefore, this study aims to systematically examine how digital storytelling enhances student engagement and motivation in English learning. This research employed a Systematic Literature Review (SLR) following the PRISMA framework. Articles published between 2020 and 2025 were collected through Publish or Perish as the primary source, supported by Google Scholar, Connected Papers, and Semantic Scholar. Based on predetermined inclusion and exclusion criteria, 12 articles were selected and analyzed using thematic analysis. The findings reveal that digital storytelling enhances engagement across behavioral, cognitive, and emotional dimensions. Students become more active in language activities, demonstrate deeper understanding, and show greater enthusiasm during learning. It also strengthens intrinsic motivation by presenting contextual and relatable stories that foster enjoyment, confidence, and a sense of ownership. Student involvement in creating digital stories further promotes creativity, critical thinking, collaboration, and responsibility. Therefore, digital storytelling is a flexible and sustainable strategy for improving engagement and intrinsic motivation in young learners’ English learning.